Accelerating the Search for Interventions Aimed at Expanding the Health Span in Humans: The Role of Epidemiology. (13th November 2019) - Newman, Anne B; Kritchevsky, Stephen B; Guralnik, Jack M; Cummings, Steven R; Salive, Marcel; Kuchel, George A; Schrack, Jennifer; Morris, Martha Clare; Weir, David; Baccarelli, Andrea; Murabito, Joanne M; Ben-Shlomo, Yoav; et al.
Abstract: Background: Extensive work in basic and clinical science suggests that biological mechanisms of aging are causally related to the development of disease and disability in late life. Modulation of the biological mechanisms of aging can extend both life span and health span in animal models, but translation to humans has been slow. Methods: Summary of workshop proceedings from the 2018–2019 Epidemiology of Aging Workshop hosted by the Intramural Research Program at the National Institute on Aging. Results: Epidemiologic studies play a vital role to progress in this field, particularly in evaluating new risk factors and measures of biologic aging that may influence health span, as well as developing relevant outcome measures that are robust and relevant for older individuals. Conclusions: Appropriately designed epidemiological studies are needed to identify targets for intervention and to inform study design and sample size estimates for future clinical trials designed to promote health span.